2009
DOI: 10.1002/chem.200801624
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Study of Proline‐Catalyzed Intramolecular Baylis–Hillman Reactions

Abstract: The mechanisms of proline-catalyzed and imidazole-co-catalyzed intramolecular Baylis-Hillman reactions have been studied by using density functional theory methods at the B3LYP/6-31G(d,p) level of theory. A polarizable continuum model (PCM B3LYP/6-31++G(d,p)//B3LYP/6-31G(d,p)) was used to describe solvent effects. Different reaction pathways were investigated, which indicated that water is an important catalyst in the imine/enamine conversion step in the absence of imidazole. When imidazole is used as a co-cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 95 publications
0
21
0
1
Order By: Relevance
“…Catalysis of the aldol reaction by proline analogs, including bicyclic prolines,5 heteroatom-substituted prolines,4c prolinamides,6 prolinol ethers7, and amine-, ammonium-, and tetrazole-functionalized pyrrolidines8 (Figure 1), have also been studied computationally. Computational investigations of the Mannich,9 Michael addition,6e, 7b, 10 and Morita-Baylis Hillman11 reactions by proline catalysts have also been reported.…”
Section: Introductionmentioning
confidence: 98%
“…Catalysis of the aldol reaction by proline analogs, including bicyclic prolines,5 heteroatom-substituted prolines,4c prolinamides,6 prolinol ethers7, and amine-, ammonium-, and tetrazole-functionalized pyrrolidines8 (Figure 1), have also been studied computationally. Computational investigations of the Mannich,9 Michael addition,6e, 7b, 10 and Morita-Baylis Hillman11 reactions by proline catalysts have also been reported.…”
Section: Introductionmentioning
confidence: 98%
“…Hence, the application of DFT became instrumental in theoretical studies of mechanisms in metalmediated catalysis. [6][7][8][9][10][11][12][13][14] Yet, the treatment of open-shell systems 16,18,19 and (near-)degenerate states remains a challenge for DFT. 15 Failures of approximate exchange-correlation density functionals in predicting properties of open-shell systems have been traced to the delocalization error and static correlation error 17,20 which are rooted in an inappropriate behavior of the energy with respect to fractional charges and fractional spins.…”
Section: Introductionmentioning
confidence: 99%
“…Subtle details of this mechanism have come to light as a consequence of an extensive density functional analysis at the B3LYP/6-31-G(d,p) level which included the use of the polarized continuum model (PCM B3LYP/6-31++G(d,p)//B3LYP/6-31G(d,p)) to describe solvent effects, the most important being the role played by water to give rise to the required syn and anti , ( E,Z )-dienamine key intermediates in equilibrium, as the theoretical calculations demonstrated that ( E,E )-enamines could not undergo cyclization [ 150 ]. According to these PCM calculations, the cyclization of the anti , E,Z -dienamine is biased towards the formation of the ( S )-configured product, as illustrated in Scheme 14 which displays, in a simplified manner, the modifications introduced by the computational work by Gil Santos et al ., in close analogy with the model proposed and by List and coworkers [ 151 ].…”
Section: The α-Aminoacid Catalyzed and α-Aminoacid-amine Cocatalyzmentioning
confidence: 99%
“…), have recently been added to the above armoury of bifunctional organocatalysts [ 69 , 70 , 71 , 72 ]. Obviously, from a mechanistic viewpoint these α-amino acid-organocatalyzed MBH reactions differ completely to those categorized as standard MBH and aza-MBH reactions which involve tertiary amine or phosphine catalysts [ 73 , 74 , 75 ].…”
Section: Introductionmentioning
confidence: 99%